(untitled) (New York, 1998)
There has never been a single definitive source of key information on all facets of discrete-event simulation and its applications to major industries. The Handbook of Simulation brings together the contributions of leading academics, practitioners, and software developers to offer authoritative coverage of the principles, techniques, and uses of discrete-event simulation.
Mô hình hóa và phân tích hệ thống xử lý môi trường,Mô hình và mô phỏng trong quản lý tài nguyên và nông nghiệp
Keywords: Simulation methods,Discrete-time systems,Phương pháp mô phỏng,Hệ thống thời gian riêng biệt; Handbooks, manuals, etc.,Handbooks, manuals, etc.,Sổ tay, cẩm nang, v.v...,Sổ tay, cẩm nang, v.v...